SYNTHESIS OF CHARACTER BUILDING MODELS THROUGH ISLAMIC RELIGIOUS EDUCATION CURRICULUM: A SYSTEMATIC LITERATURE REVIEW - Erihadiana, Mohammad; Rizky Ramadhani, Annanda Muhamad; Hasilah, Fauzah Nurul; Aulia, Nabila Putri (Khatulistiwa, 2025)
This Systematic Literature Review (SLR) investigates PAI curriculum alignment with national character development goals. PAI implementation struggles to adapt to 21st-century digital competence demands, forming the main gap. Utilizing an SLR protocol, articles (2020–2025) were analyzed to synthesize curriculum dynamics and relevance gaps. Findings confirm a critical disjunction between PAI’s spiritual objectives and digital skills necessity. The primary contribution is the Synthesis of a novel Character Building Model, integrating PAI values with competence-based learning frameworks, offering practical guidance for policymakers and educators.